Association between thyroid stimulating hormone levels and nonproliferative diabetic retinopathy: a cross-sectional study - Yiqi Xu; Biwu Dong; Youyun Tang; Yan Jiang; Tingting Huang; Feng Jiang; Wei Xing; Junsheng Chen; Fengping Zhu (BMC Endocrine Disorders)
Abstract Background The association between thyroid-stimulating hormone (TSH) and type 2 diabetes mellitus (T2DM) is well known. However, whether TSH is related to nonproliferative diabetic retinopathy (NPDR) has not been studied. This study aimed to explore the relationship between TSH and NPDR in Chinese patients with T2DM. Methods In this cross-sectional study, 427 patients with T2DM were enrolled. The individuals were classified into two groups according to the fundus oculi examination: the non-diabetic retinopathy (NDR) group (n = 224) and the non-proliferative diabetic retinopathy (NPDR) group (n = 203). The individuals’ demographic and clinical data were collected by reviewing medical records and direct interviews. The demographic data and biochemical parameters were compared between groups using the Student’s t - test or the Mann‒Whitney U test, anthropometric measurements, thyroid function, and NPDR were evaluated, and the associations between TSH and NPDR were assessed using logistic regression models. Results No significant differences in age, sex, body mass index (BMI), incidence of alcohol consumption, and duration of diabetes were found between these two groups. The systolic blood pressure (SBP), incidence of smoking, TSH, blood urea nitrogen (BUN), and urinary micro-albumin (mALB) were significantly higher in the NPDR group than in the NDR group (P < 0.05). Individuals in the NDR group had higher levels of thyroxine (T4), glutamic pyruvic transaminase (ALT), fasting C-peptide (FCP), and 2-hour C-peptide (2hCP) than individuals in the NPDR group (P < 0.05). Spearman’s correlation analysis revealed that the serum TSH levels were negatively associated with the HbA1c levels in all patients (r=-0.11, P < 0.05). Serum TSH levels were negatively correlated with HbA1c levels (r = -0.19, P < 0.01) and positively correlated with diabetes duration (r = 0.14, P < 0.05) in the NPDR group. Multivariate logistic regression analysis revealed that high TSH levels, sex, diabetes duration, high-density lipoprotein cholesterol (HDL-C), glycosylated hemoglobin (HbA1c), FCP, and SBP were associated with NPDR [odds ratio (OR) > 1, P < 0.05]. Receiver operating characteristic curve analysis revealed that the optimal cutoff point of TSH for predicting NPDR was 2.235 mIU/L. Conclusion The TSH level is independently associated with NPDR in the Chinese population with T2DM. A high serum TSH level may be a potential risk factor for NPDR and an indicator for screening for diabetic microangiopathy. Trial registration This study is registered with the Chinese Clinical Trial Registry (02/21/2025 ChiCTR2500097614).